A Gender Based Analysis of Communication Styles in Ariana Grande’s Podcast Interview - Neshka, Neshka Rizkita Tamara Putri; Garnida, Susie Chrismalia (Fakultas Ilmu Budaya Universitas 17 Agustus 1945 Surabaya, 2025)
This study examines the gender based communication differences in the podcast interview titled “Ariana Grande NewAlbum ‘Eternal Sunshine,’ Wicked, Glinda Part 1.” The researchaims to identify the contrasting linguistic features used by male and female speakers, drawing from Lakoff’s theory for women’sspeech and Coates’ framework for male communication. The datawere collected by transcribing the podcast and analyzing relevantutterances using a qualitative descriptive method. The findingsreveal that male speakers frequently use commands, directquestions, and minimal responses, whereas female speakers tend to employ intensifiers, hedges, and emphatic stress. These results reinforce the idea that gender significantly influences conversational style. However, overlapping language features were also found, indicating that context and conversational dynamics contribute to linguistics choices. The study highlights the importance of podcasts as platforms for spontaneous, unscripted dialogue, making them ideal for linguistic analysis